Spinal transection alters external urethral sphincter activity during spontaneous voiding in freely-moving rats. - LaPallo, Brandon K.; Jonathan Wolpaw; Xiang Yang Chen; Jonathan S. Carp (Journal of neurotrauma, 2017)
The rat is a commonly used model for the study of lower urinary tract function before and after spinal cord injury. We have previously reported that in unanesthetized, freely-moving rats, although phasic external urethral sphincter (EUS) activity (bursting) is most common during micturition, productive voiding can occur in the absence of bursting, which differs from results seen in anesthetized or unanesthetized restrained animals. The purpose of the present study was to characterize EUS behavior in unanesthetized, freely-moving rats before and after mid-thoracic (T8) or thoraco-lumbar (T13-L1) spinal transection to determine how EUS behavior after spinal cord injury differs from that seen in anesthetized or unanesthetized restrained rats. Several abnormalities became evident that were comparable after transection at either level including: repetitive non-voiding EUS contractions; increased prevalence, intensity and duration of EUS bursting; decreased rate of urine evacuation during bursting; increased void size and decreased number of daily voids; shorter inter-burst silent period and increased frequency of bursting; and loss of the direct linear relationships that are evident in intact animals between void size and bursting silent period. These data suggest that transection-induced delayed initiation of EUS bursting allows co-contraction of the bladder and the EUS that prevents or limits urine evacuation, resulting in a detrusor-sphincter dyssynergia-like phenomenon. In addition, the higher-than-normal frequency at which EUS bursting occurs after transection is associated with shorter silent periods during which urine typically flows, which interferes with voiding by slowing the rate of urine evacuation. That results were comparable after either transection suggests that the central pattern generator responsible for EUS bursting is located caudal to the L1 spinal segment.